Emerging roles of RAC1 in treating lung cancer patients. Issue 4 (24th November 2016) - Zou, T.; Mao, X.; Yin, J.; Li, X.; Chen, J.; Zhu, T.; Li, Q.; Zhou, H.; Liu, Z.
Abstract : The Ras‐related C3 botulinum toxin substrate 1 ( RAC1 ), a member of the Rho family of small guanosine triphosphatases, is critical for many cellular activities, such as phagocytosis, adhesion, migration, motility, cell proliferation, and axonal growth. In addition, RAC1 plays an important role in cancer angiogenesis, invasion, and migration, and it has been reported to be related to most cancers, such as breast cancer, gastric cancer, testicular germ cell cancer, and lung cancer. Recently, the therapeutic target of RAC1 in cancer has been investigated. In addition, some investigations have shown that inhibition of RAC1 can reverse drug‐resistance in non‐small cell lung cancer. In this review, we summarize the recent advances in understanding the role of RAC1 in lung cancer and the underlying mechanisms and discuss its value in clinical therapy. Abstract : In this review, we summarized the association between the Ras‐related C3 botulinum toxin substrate 1 (RAC1) and lung cancer. We overview the classical binding cycle of RAC1 and GTP/GDP. We also summarized the upstream regulators and downstream effectors of RAC1. Also we highlight the feasibility of RAC1 in treating lung cancer patients as a novel drug target, which may provide an important clue for future lung cancer treatments.